Setting research priorities for English as an additional language: what do research users want from EAL research? - Chalmers, H; Faitaki, F; Murphy, V (John Benjamins Publishing, 2023)
We report a priority setting partnership (PSP), which sought to establish the priorities for new research among research users (educators, parents, and learners) in the field of English as an Additional Language (EAL). A steering committee consisting of members of these research user groups was established to oversee the project. An online ‘uncertainty questionnaire’ was distributed to research users inviting them to identify areas of their practice about which they are uncertain. These ‘raw’ uncertainties were consolidated and converted into a list of research questions, which was then distributed to the same groups to rank in order of priority. The 25 highest ranked questions were then discussed and debated in a workshop, consisting of research user representatives, to collectively and democratically produce a final Top 10 list of questions. The Top 10 shows what EAL research users regard as priorities, which we hope will inform research agendas and funding decisions.